DIGITALIZATION TRAINING CHRONIC DISEASE PATIENT MEDICAL RECORD DOCUMENTS FOR HEALTH CENTERS - Maula Ismail Mohammad; Yanto Haryanto (Ann Publisher, 2024)
Digitization of medical record documents of patients with Diabetes Mellitus (DM) is switching media from manual (paper) to electronic using a scanner. When the implementation of electronic medical records is already running, the patient's previous medical records are not eliminated or forgotten because the content is important, including the patient's medical history. To support the control of DM disease, this patient's medical history may be needed again at any time to see the patient's previous health records that may be continuous. While the last patient's medical records were manually using paper, they are no longer by current technological developments. Digitization of medical record documents is a solution related to this. The digitization of medical record documents at the Puskesmas has not yet been implemented because there is no system associated with the digitization of medical record documents. From this explanation, the devotees are interested in participating in DM control by providing DRM digitization training for DM patients at the Health Center.